Evaluation of double locus (clfB and spa) sequence typing for studying molecular epidemiology of methicillin-resistant Staphylococcus aureus in Taiwan - Chen-Cheng Huang; Cheng-Mao Ho; Hui-Chen Chen; Chi-Yuan Li; Ni Tien; Hsiu-Mei Fan; Mao-Cheng Ge; Jang-Jih Lu (Journal of Microbiology, Immunology and Infection, 2017)
Background: Pulsed-field gel electrophoresis (PFGE) is the “gold standard” for epidemiological investigation of methicillin-resistant Staphylococcus aureus (MRSA), but several DNA sequence-based methods have been developed in MRSA typing because of the unambiguous results. Methods: Ninety-one MRSA isolates were collected from the blood cultures of different patients from July 2008 to December 2008 in central Taiwan. The molecular characteristics of each isolate, including double locus sequence typing (DLST; spa and clfB typing), Staphylococcus cassette chromosome mec (SCCmec), and PFGE were determined for comparison. Results: Five major clfB types (types A–E), 18 spa types, 33 DLST genotypes, five SCCmec types, 17 pulsotypes have been observed. Three major DLST genotypes (A1-t002, C0-t037, and B1-t437) and two major pulsotypes (6 and 8) were identified. Most clfB type A isolates (97.1%) were SCCmec type II and all clfB type C isolates (100%) were SCCmec type III. Most clfB type B isolates (88.9%) were SCCmec type IV (59.3%) and VT (29.6%). All (100%) clfB subtypes A1, A2, and C isolates and 70.4% of clfB type B isolates belonged to healthcare-associated-MRSA. The average congruence was 57.7% between DLST and PFGE, and 96.6% between clfB and SCCmec type. The index of discrimination of SCCmec, clfB, spa, PFGE, and DLST was 0.72, 0.79, 0.80, 0.81, and 0.87, respectively. Conclusion: ClfB type has high congruence with SCCmec type. The DLST method in this study yielded a higher discriminatory power than PFGE in local investigation of molecular epidemiology of MRSA and a promising alternative to PFGE.